TEACHERS AND PRINCIPALSâ€™ PERCEPTION TOWARDS THE IMPLEMENTATION OF FULLY PRIVATELY RUN PUBLIC SCHOOLS - Kamaruzzaman Ismail; Sheikh Muhamad Hizam Sheikh Khairuddin; Zalina Zainudin, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The objective of this paper is to identify teachers and principalsâ€™ perception towards the implementation of fully privately run public schools (FPRPS) in Malaysia. Under the Malaysian Educational Blueprint (MEB) 2013 - 2025, it is clear that the programmes and activities that would encourage and allow parents, the public and private sectors, NGOs, and society to forge a partnership with the school will benefit especially concerning values education. These school community partnerships can be related to the ninth shift in the Blueprint which is â€œpartnering with parents, community and private sector at scale,â€ although, the emphasis of this shift is more on studentsâ€™ academic progress. This study was conducted for three months periods, involving 87 teachers and principals, 13 schools in 3 Districts Education Office (PPD) which are Petaling Utama, Wilayah Bangsar-Pudu and Hulu Langat, 11 private sectors and 10 regulatory bodies. The qualitative method was used in this study where the interview (in form of focus group discussion â€“FGD) has been implemented for teachers and principals. The data had been processed by using Atlas to â€“ Windows 8 and Statistical Package for the Social Sciences (SPSS). From the interviews conducted on FPRPS, all of the respondents (i.e. teachers and principals) indicated that they are not aware of FPRPS and are ready and willing to accept the FPRPS implementation. This is because FPRS offers huge potential benefits to them. These include improvement in studentsâ€™ skill, teacher training, academic performance, employability, financial support, infrastructures, facilities, security, maintenance, workload, school efficiency, productivity, teachersâ€™ skill, profit, and salary.